2002
DOI: 10.1054/jhsb.2002.0782
|View full text |Cite
|
Sign up to set email alerts
|

Visual Estimation of Finger Angles: Do we Need Goniometers?

Abstract: Seventy-one plastic surgeons and therapists, of varying levels of seniority and experience, were asked to examine a resin cast of an adult male hand and use estimation to measure the angles of the metacarpophalangeal and interphalangeal joints of each digit. Visual estimation by all subjects was inaccurate by a mean of approximately 25% (median percentage error 22, range 1-100). Consultants were the most accurate, whilst physiotherapists were the least. Regular goniometer users were no more accurate. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…Previous studies have examined the accuracy of VE of deformity, and even though orthopaedic surgeons may be more accurate than the general community this method remains relatively inaccurate . Moran et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have examined the accuracy of VE of deformity, and even though orthopaedic surgeons may be more accurate than the general community this method remains relatively inaccurate . Moran et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the accuracy of VE of deformity, [14][15][16] and even though orthopaedic surgeons may be more accurate than the general community this method remains relatively inaccurate. 14 Moran et al 15 reported that the number of years of orthopaedic experience was unrelated to the validity and reliability of VE of angles, and found angles less than 31 degrees were consistently overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The inaccuracy of visual estimates of finger angles has been previously documented as 25% when compared to computer-based joint assessment [33]. Nonetheless the Contompasis Score displayed poorer intra-and inter-rater reliability compared to the Beighton score.…”
Section: Discussionmentioning
confidence: 97%
“…Due to skin mobility and suppleness, however, it seems difficult to achieve steadiness of the joint angle with palmar supports alone. The use of hand cast [24], transarticular pinning of the cadaver finger joints in various degrees of flexion [31], and wooden finger joints [35] is arguably too artificial. Only one study used change of finger motion due to a treatment to test inter-goniometer reliability [6].…”
Section: Methodsmentioning
confidence: 99%